Peningkatan Keterampilan Berpikir Tingkat Tinggi (Higher Order Thinking Skills) Peserta Didik Menggunakan Modul Pembelajaran Fisika Yang Berbasis Pendekatan Saintifik Materi Suhu Dan Perubahannya - Midah Nurhidayah; Febri Listianingrum; Wahyu Kumala Sari (Universitas Cenderawasih, 2023)
The purpose of this study is to find out the increase in the HOTS of students using learning modules based on a scientific approach to the material of temperature and its changes. The sample taken in this study was 34 students of grade 7 MTs. Jayapura City State. This study uses a classroom action research method that uses 3 cycles to determine the increase in HOTS. The results showed that in learning using the module, students' HOTS increased with the n-Gain value of the cycle (1) of 0.57, (2) of 0.58, and (3) of 0.64 with an average n-Gain value. of 0.60 medium categories. Based on this, it can be concluded that students have sufficient higher-order thinking skills (HOTS).